IMPLEMENTATION OF TEACHER EXAMPLE METHOD IN LEARNING ISLAMIC RELIGIOUS EDUCATION AT SMP NEGERI 2 GEMOLONG - Abbas, Ngatmin; Khoir, Mulyanto Abdullah (Proceeding of International Conference of Islamic Education, 2023)
The teaching of Islamic Religious Education (IRE) at SMP Negeri 2 Gemolong, Sragen Regency, has implemented the method of teacher exemplarity as an alternative to enhance the effectiveness of the learning process. The survey results indicate that 69.1% of students stated that their teachers always relate IRE lessons to their daily lives. Furthermore, observations of the teachers revealed that they have successfully applied the method of teacher exemplarity in IRE instruction. The effectiveness of this approach is evident from the fact that 75% of students have achieved or surpassed the Minimum Completion Criteria (KKM) set by the school. Thus, the method of teacher exemplarity can be considered as an effective alternative to enhance the teaching and learning of Islamic Religious Education in the school. Additionally, SMP Negeri 2 Gemolong can serve as a pilot project for strengthening students' character.